2016
DOI: 10.1515/dmpt-2016-0008
|View full text |Cite
|
Sign up to set email alerts
|

Altered pharmacokinetics of rosiglitazone in a mouse model of non-alcoholic fatty liver disease

Abstract: The NAFLD mouse model showed profound effects on rosiglitazone pharmacokinetics. The magnitude of change in rosiglitazone pharmacokinetics is similar to that observed in humans with moderate to severe liver disease. The present animal model can be utilized to study the NAFLD-induced changes in the pharmacokinetics of different drugs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…1 D,E). Notably, the doses used compare well with daily human recommended doses, given the differences in the pharmacokinetics of the three drugs in the mouse and human systems [ 41 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…1 D,E). Notably, the doses used compare well with daily human recommended doses, given the differences in the pharmacokinetics of the three drugs in the mouse and human systems [ 41 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, the direction of change is not clear as both increasing and decreasing trends have been observed (Fisher et al , 2009, Li et al , 2016). The AUC of rosiglitazone, an insulin sensitizer and a substrate of CYP2C8 and CYP2C9 (Baldwin et al , 1999), was found to be significantly increased in male mice after high fat and high fructose NAFLD induction (Kulkarni et al , 2016). Nevertheless, it is not clear whether this increase was mediated through down-regulation of the CYP2C8/9 or alteration in transport mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…Greater hepatotoxicity of rosiglitazone in some obese patients might also be secondary to an alteration in its pharmacokinetics, which might favor higher plasma concentrations and PPARγ overactivation in the liver. In keeping with this hypothesis, the plasma halflife of rosiglitazone was nearly tripled in a mouse model of diet-induced obesity [91]. Rosiglitazone mainly undergoes CYP2C8-mediated p-hydroxylation and N-demethylation, followed by sulfate and glucuronide conjugation [92], metabolic pathways that might be affected in obesity.…”
Section: Thiazolidinedionesmentioning
confidence: 83%